1989
DOI: 10.2136/sssaj1989.03615995005300060034x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crop Production on the Physical Status of a Typic Albaqualf

Abstract: Extensive tillage during long periods of time affects soil productivity by altering soil properties. Quantitative measurements were made to determine the combined effects of duration of tillage and production of soybean [Glycine max. (L.)] and rice (Oryza sativa) on selected physical and chemical properties of a Crowley silt loam (fine, montmorillonitic, thermic Typic Albaqualf). Four adjacent fields were sampled which included a virgin prairie and three fields in cultivation for 1, 12, and 30 yr. Undisturbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
4
12
0
4
Order By: Relevance
“…This might be attributed to the higher clay content for more depths at the Field site (table 1). A similar trend was found by Scott and Wood (1989) in a study in silt loam (Albaqualf) soils; they found that for surface soil under cultivation for 30 years and a virgin prairie, soil water retention at -30 and -1,500 kPa (-4.4 to -217.6 lb in -2 ) were not significantly different, whereas water retention was significantly different for other pressures (higher water pressures).…”
Section: Saturated Hydraulic Conductivity Resultssupporting
confidence: 85%
“…This might be attributed to the higher clay content for more depths at the Field site (table 1). A similar trend was found by Scott and Wood (1989) in a study in silt loam (Albaqualf) soils; they found that for surface soil under cultivation for 30 years and a virgin prairie, soil water retention at -30 and -1,500 kPa (-4.4 to -217.6 lb in -2 ) were not significantly different, whereas water retention was significantly different for other pressures (higher water pressures).…”
Section: Saturated Hydraulic Conductivity Resultssupporting
confidence: 85%
“…Conforme Hajabbasi et al (1997), essas condições provocam decréscimo da macroporosidade, contribuindo para uma elevação nos valores da densidade do solo. O aumento da densidade do solo devido ao cultivo também pode estar relacionado com a perda de matéria orgânica (Bauer & Black, 1981;Scott & Wood, 1989). A atividade microbiana foi alterada pelo cultivo do solo (Figura 7).…”
Section: Resultados Similares Foram Apresentados Por Borges and Kiehlunclassified
“…Com a retirada da vegetação natural e implantação das culturas comerciais, ocorrem modificações nas propriedades dos solos. A magnitude e a direção dessas modificações dependem do tipo de solo, do clima, do cultivo e do sistema de manejo utilizado (Scott & Wood, 1989). Estudos nesse sentido foram realizados por Borges & Kiehl (1997), os quais constataram que os cultivos de banana e citros elevaram os teores de cátions no solo, principalmente no horizonte superficial de um Latossolo Amarelo álico.…”
Section: Introductionunclassified
“…Recent developments in availability of irrigation water and the appearance of soybean rust (Phakopsora pachyrhizi) in the U.S. South might promote continuous cropping of rice, at least in fields near water bodies. Increased SOM levels under continuous rice cropping might also improve soil physical properties, thereby mitigating long-term degradation under the riceÀsoybean rotation (Scott and Wood, 1989). In a 4-yr field trial, however, grain yield of a continuous rice rotation was 19% (1.5 ton/ha) less than the grain yield of rice following soybean (Anders et al, 2004).…”
Section: Continuous Rice Rotation In Arkansas Usamentioning
confidence: 99%